Accurate Magnetic Shell Approximations with Magnetostatic Finite Element Formulations by a Subdomain Approach - Quoc, V. D. (Engineering, Technology & Applied Science Research, 2020)
This paper presents a subproblem approach with h-conformal magnetostatic finite element formulations for treating the errors of magnetic shell approximation, by replacing volume thin regions by surfaces with interface conditions. These approximations seem to neglect the curvature effects in the vicinity of corners and edges. The process from the surface-to-volume correction problem is presented as a sequence of several subdomains, which can be composed to the full domain, including inductors and thin magnetic regions. Each step of the process will be separately performed on its own subdomain and submesh instead of solving the problem in the full domain. This allows reducing the size of matrix and time computation.